Pengembangan Bahan Ajar Pendidikan Agama Islam Berbasis Multiliterasi di Sekolah Menengah Pertama Islam Terpadu Sahabat Al-Quran Binjai - Hairil Anwar; Rusyidi Ananda; Muhammad Rifa’i (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The aim of this research is to evaluate three main aspects: first, the suitability of Islamic Religious Education materials which apply a multiliteracy approach to improve student learning outcomes; second, ease of use of Islamic Religious Education materials with a multiliteracy approach in improving student learning outcomes; and third, the efficiency of Islamic Religious Education materials which utilize a multiliteracy approach to achieving student learning outcomes. This research was carried out at the Sahabat Qur'an Binjai IT Middle School during the first semester of the 2023-2024 academic year. The research method used is the development method using the Sugiyono model. The test subjects for this research were class VIII students, with a focus on developing multiliteracy-based PAI material. The resulting material has gone through a validation process by design experts, material experts and language experts, with an average validation result of 3.66 and a